The Turkish War of Independence - Erickson, Edward J., 1950- (Santa Barbara, California)
xxvi, 399 sayfa
Keywords: “The dramatic story of the turbulent birth of modern Turkey which rose out of the ashes of the Ottoman Empire to fight off Allied occupiers, Greek invaders, and internal ethnic groups to proclaim a new republic under Mustafa Kemal.“--